2005
DOI: 10.1042/cs20040281
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of reactive oxygen species (ROS) production by C18 fatty acids in Jurkat and Raji cells

Abstract: In the present study, the effects of C18 fatty acids with different numbers of double bonds, SA (stearic acid; C18:0), OA (oleic acid; C18:1), LA (linoleic acid; C18:2) and gamma-LNA (gamma-linolenic acid; C18:3), on ROS (reactive oxygen species) production by Jurkat (a human T-lymphocyte-derived cell line) and Raji (a human B-lymphocyte-derived cell line) cells were investigated. ROS production was determined by NBT (Nitro Blue Tetrazolium) reduction (intracellular and extracellular ROS production) and by dih… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
37
0
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(43 citation statements)
references
References 77 publications
5
37
0
1
Order By: Relevance
“…Our results showing that vitamin C and NAC inhibit the stimulatory effect of LA on LOX-1 protein expression clearly identify endothelial LOX-1 as a novel oxidative stress-sensitive target for LA. In agreement with previous studies (36,37), we found that NADPH oxidase inhibitors prevented LA-induced protein expression, thus indicating that NADPH oxidase is one of the enzymatic superoxide sources activated by LA. Considering the potential key role of LOX-1 in ED, these results further support the concept that oxidative stress may constitute an important mechanism responsible for LA-mediated ED.…”
Section: Discussionsupporting
confidence: 81%
“…Our results showing that vitamin C and NAC inhibit the stimulatory effect of LA on LOX-1 protein expression clearly identify endothelial LOX-1 as a novel oxidative stress-sensitive target for LA. In agreement with previous studies (36,37), we found that NADPH oxidase inhibitors prevented LA-induced protein expression, thus indicating that NADPH oxidase is one of the enzymatic superoxide sources activated by LA. Considering the potential key role of LOX-1 in ED, these results further support the concept that oxidative stress may constitute an important mechanism responsible for LA-mediated ED.…”
Section: Discussionsupporting
confidence: 81%
“…This time course fits with those of previous works (37)(38)(39), which reported early ROS production within 1 or 2 h after postprandial hypertriglyceridemia or after fatty acid in vitro exposure in circulating leukocytes or in lymphocytederived and pancreatic cell lines, respectively. Thus, lipids can rapidly stimulate elevation of intracellular ROS levels in numerous cell populations.…”
Section: Diabetes Vol 56 January 2007supporting
confidence: 78%
“…Furthermore, it promotes apoptosis through interfering with mitochondrial oxidative phosphorylation [36] and influencing the permeability of the mitochondrial membrane via Bax [37][38][39]. Oleic acid has also been described to increase the production of reactive oxygen species [38,40,41] and to inhibit the activation of NF-κB and thereby lead to increased apoptosis [42]. Moreover, oleic acid leads to p53-dependent apoptosis in Jurkat-cells [43] and it has been shown to activate peroxisome proliferator activated receptors which again results in increased cell death [44][45][46][47].…”
Section: Discussionmentioning
confidence: 99%